A property of solutions to linear monopoly problems - Gregory Pavlov (The University of Western Ontario, Department of Economics, 2010)
We extend the 'no-haggling' result of Riley and Zeckhauser (1983) to the class of linear multiproduct monopoly problems when the buyer's valuations are smoothly distributed. In particular we show that there is no loss for the seller in optimizing over mechanisms such that all allocations belong to the boundary of the feasible set. The set of potentially optimal mechanisms can be further restricted when the costs are sufficiently low: the optimal mechanisms use only allocations from the 'north-east' boundary of the feasible set and the null allocation.
Keywords: C78; D42; D82; L11; 330; multidimensional screening; price discrimination; optimal selling strategies; mechanism design; Monopol; Verkauf; Preisdifferenzierung